Efektivitas Model Problem Based Learning Ditinjau dari Kemampuan Komunikasi Matematis Siswa - Saputri, Suci Indah; Caswita, Caswita; Widyastuti, Widyastuti (Jurnal Pendidikan MIPA, 2018)
The Effectiveness of The Problem Based Learning Model in Terms of Students Mathematical Communication Skills. This research aimed to examine the effectiveness of the problem based learning (PBL) model in terms of students mathematical communication skills. The samples of this research were students of VIII D as many 32 students as experiment class and VIII-D as many 29 students as control class which were chosen by cluster random sampling technique. This research used randomized pretest-posttest control group design. The research data was obtained by test technique through mathematical communication skills tests instrument which form essay question. Reaserch data analized using One Side Proportion Test and Mann Whitney U test. By the rasults of data analysis the students who got score 71 or more of mathematical communication skill in PBL class were not more than 60% of all students in that class. Gain score mathematical communication skill who treated by PBL more than the students who treated by non PBL. The conclusion of this research is that the PBL model was not effective in term of students mathematical communication skills, but the student’s mathematical communication skills who took PBL was higher than students who took non PBL.keywords: problem based learning, mathematical communication, effectivenes DOI: http://dx.doi.org/10.23960/jpmipa/v19i2.pp99-110